Clinical Supervision To Overcome Teachers Experiencing Demotivation - Siti Nur Aviatun Hasanah; Maulidatul Adzimah; Ahmad Rausyan Fikri; Moh Rofik; Robert Edy Sudarwan (Civiliza Publishing, Indonesia., 2026)
Teacher demotivation is a common challenge in many educational institutions. Increasing administrative burdens, demands for technology, curriculum changes, and a lack of professional support have led some teachers to experience decreased teaching enthusiasm, boredom, and reduced creativity in learning. These conditions have the potential to impact the quality of the teaching and learning process and the achievement of educational goals. This study aims to analyze the conditions of teacher demotivation, the implementation of clinical supervision, and the role of clinical supervision in addressing teacher demotivation. The study used a qualitative approach with a case study type. Data were obtained through observation, interviews, and documentation involving the principal, vice principal for curriculum, and teachers who were the targets of clinical supervision. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results showed that teacher demotivation was characterized by decreased teaching enthusiasm, the emergence of boredom, and reduced creativity in learning. Clinical supervision was implemented through initial meetings, classroom observations, feedback discussions, and follow-up with a collaborative and humanistic approach. The implementation of clinical supervision has been proven to help teachers identify problems, increase self-confidence, obtain constructive feedback, and revitalize work motivation. The implications of this research indicate that clinical supervision can be an effective coaching strategy in supporting teachers' psychological well-being, improving professionalism, and maintaining the quality of learning sustainably in the school environment